2002
DOI: 10.1103/physrevlett.89.268303
|View full text |Cite
|
Sign up to set email alerts
|

Linear and Time-Dependent Behavior of the Gyrotron Backward-Wave Oscillator

Abstract: Formation of axial modes in the gyrotron backward-wave oscillator is examined in the perspective of optimum conditions for beam-wave interactions. Distinctive linear properties are revealed and interpreted physically. Nonlinear implications of these properties (specifically, the role of high-order axial modes) are investigated with time-dependent simulations. Nonstationary oscillations exhibit self-modulation behavior while displaying no evidence of axial mode competition. Reasons for the erratic frequency tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 22 publications
1
17
0
1
Order By: Relevance
“…3 The time-dependent simulation also showed that the onset current can be more than 100 times the start oscillation current of the gyro-BWO with a uniform waveguide, and the onset current for the nonstationary oscillations can be higher with a shorter length at no expense to the interaction efficiency. 25 Previous studies have revealed some essential properties of the gyro-BWO, and the stable operation regimes were also demonstrated by the theoretical analysis 25 and experiments. 10 However, there are some unresolved issues needed to be further studied for getting a more in-depth understanding of the intriguing electrodynamical system.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…3 The time-dependent simulation also showed that the onset current can be more than 100 times the start oscillation current of the gyro-BWO with a uniform waveguide, and the onset current for the nonstationary oscillations can be higher with a shorter length at no expense to the interaction efficiency. 25 Previous studies have revealed some essential properties of the gyro-BWO, and the stable operation regimes were also demonstrated by the theoretical analysis 25 and experiments. 10 However, there are some unresolved issues needed to be further studied for getting a more in-depth understanding of the intriguing electrodynamical system.…”
Section: Introductionmentioning
confidence: 90%
“…Theoretical and simulation works were then motivated by experiments for studying the essential properties of gyro-BWO, e.g., the start oscillation criteria (linear properties), [14][15][16] the saturation efficiency of the beamwave interaction, [17][18][19][20][21][22][23] and the nonstationary oscillation of the gyro-BWO (nonlinear properties). 24,25 The theoretical analysis and numerical simulation formed the basis of the experimental design and have been extensively applied on the study of the efficiency enhancement of gyro-BWO induced by the magnetic field tapering 18,19,21 or the tapering of waveguide wall radius. 22 The physical processes in the gyro-BWO are quite complicated and were scarcely discussed in previous literatures before 1990s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolute instability occurs only at a discrete set of frequencies determined by the phase coherence within the internal feedback loop. 21 Hence, it is not a common phenomenon in a cavity-based gyrodevice, which has a different set of resonant frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…For a comprehensive discussion on this topic we refer to [6][7][8][9]. It suffices only to recall here that one of the effective means for frequency tunability is based on the mechanism which involves excitation of a sequence of forward- [10] or backward-wave [10][11][12] high-order axial modes (HOAM). The results of the present study show that the uptapered resonators are beneficial in this respect too since they allow HOAM to be excited at higher efficiency levels.…”
mentioning
confidence: 99%